Hubungan Prestasi Akademik Dan Faktor Eksternal Dengan Kelulusan Uji Kompetensi Mahasiswa Keperawatan Stikes Jenderal Achmad Yani Yogyakarta - Deby Zulkarnain Rahadian Syah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2017)
Objective: to know the relationship of academic achievement and external factors with the graduation of competency test of nursing students Stikes General Achmad Yani YogyakartaMethods: this research is an associative descriptive research. This research was conducted at Stikes General Achmad Yani Yogyakarta. The data used use cross sectional approach, in the absence of any intervention and data retrieval is done one time.Result: result of correlation test between academic achievement level of bachelor degree of nursing with competence test obtained p-value 0,002. The result can be interpreted as having relationship because p-value is less than alpha (0,05). The value of close relationship in the range of categories is very strong that is 0.836. The result of correlation test between the achievement index of professional ners with competency test obtained p-value 0.106. The result can be interpreted as no relationship because p-value is more than alpha (0,05). The result of comparation test between academic factor and competence test is obtained p-value 0,001. The result can be interpreted as having relationship because p-value is less than alpha (0,05). The value (r) or the closeness of the relationship of these two variables is very strong at 1.00. Result of comparation test between environmental factor with competence test got result p-value 0,807. The result can be interpreted as no relationship because p-value is more than alpha (0,05).Conclusion: There is a relationship between IPK S1 Nursing with graduation of nurses competence test. There is no correlation between IPK Ners with the graduation of nurse competency test. There is a correlation between academic factor with passing of nurse competence test. There is no correlation between environmental factors with the passing of nurse competence test.